Multi-Omics Approaches Revealed the Associations of Host Metabolism and Gut Microbiome With Phylogeny and Environmental Adaptation in Mountain Dragons - Zhu, Wei; Qi, Yin; Wang, Xiaoyi; Shi, Xiudong; Chang, Liming; Liu, Jiongyu; Zhu, Lifeng; Jiang, Jianping (Frontiers in Microbiology, 2022)
The molecular basis enabling the adaptation of animals to spatially heterogeneous environments is a critical clue for understanding the variation, formation, and maintenance of biodiversity in the context of global climate change. Mountain dragons (Agamidae: Diploderma) thrive in the Hengduan Mountain Region, a biodiversity hotspot and a typical spatially heterogeneous environment. Here, we compare the liver and muscle metabolome and gut microbiome of eleven geographical populations from three Diploderma species (D. iadinum, D. yulongsense, and D. vela) after seven days acclimation in the same laboratory conditions. Amino acid metabolism, particularly the products of the glutathione cycle, accounted for major interspecies variations, implying its significance in genetic differentiation among mountain dragons. Notably, the cold-dwelling D. vela and D. yulongense populations tended to have higher glycerophosphate, glycerol-3-phosphocholine, and kinetin levels in their liver, higher carnosine levels in their muscle, and higher Lachnospiraceae levels in their gut. Phylogeny, net primary productivity (NPP), and the temperature had the highest explanation rate to the variations in muscle metabolome, liver metabolome, and gut microbiome, respectively, suggesting heterogeneity of biological systems in response to climatic variations. Therefore, we suggested that the organ heterogeneity in environmental responsiveness might be substantial for mountain dragons to thrive in complicated environments.